Teores de macro e micronutrientes e a relação c/n de várias espécies de plantas daninhas - Souza, Luciano S.; Velini, Edivaldo Domingues [UNESP]; Maimoni-Rodella, Rita C. S. [UNESP]; Martins, Dagoberto [UNESP] (Sociedade Brasileira da Ciência das Plantas Daninhas, 1999)
O objetivo do presente trabalho foi determinar os teores de nutrientes (N, P, K, Ca, Mg, S, Cu, Zn, Fe e Mn) e a relação C/N, presentes na matéria seca da parte aérea das seguintes espécies de plantas daninhas: Ageratum conyzoides L., Amaranthus lividus L., Bidens pilosa L., Brachiaria decumbens Stapf., Brachiaria plantaginea (Link) Hitchc., Senna occidentalis (L.) Link., Commelina benghalensis L., Cyperus rotundus L., Digitaria horizontalis Willd., Euphorbia heterophylla L., Indigofera truxillensis H.B.K., Ipomoea acuminata Roem. et Schult, Panicum maximum Jacq., Raphanus raphanistrum L., Rhynchelytrum repens (Willd.) C.E. Hubb., Richardia brasiliensis Gomez e Sida cordifolia L. Os teores de macronutrientes obtidos da matéria seca das plantas daninhas, foram maiores em geral nas dicotiledôneas. em relação às monocotiledôneas não houve um padrão de comportamento para os micronutrientes. Entretanto, o teores de carbono foram, em média, superiores para todas as monocotiledôneas, sendo que as dicotiledôneas apresentaram relações C/N menores do que as monocotiledôneas.

The aim of this work was to determine nutrient contents (N, P, K, Ca, Mg, S, Cu, Zn, Fe and Mn) as well as the CN relation found in the dry matter of the aerial parts of the following weeds: Ageratum conyzoides L., Amaranthus lividus L., Bidens pilosa L., Brachiaria decumbens Stapf., Brachiaria plantaginea (Link) Hitchc., Senna occidentalis (L.) Link., Commelina benghalensis L., Cyperus rotundus L., Digitaria horizontalis Willd., Euphorbia heterophylla L., Indigofera truxillensis H.B.K., Ipomoea acuminata Roem. et Schult, Panicum maximum Jacq., Raphanus raphanistrum L., Rhynchelytrum repens (Willd.) C.E. Hubb., Richardia brasiliensis Gomez e Sida cordifolia L. Macronutrient contents got from weeds dry matter were higher in the dycotiledons.Concerning monocotyledons there were no standard of behaviour for micronutrients. However, carbon contents were superior to all monocotyledons. Dycotiledons presented CN relation lower than monocotyledons did.
Contents of macronutrients and micronutrients and CN relation of several weed species
Keywords: biologia; nutrição mineral; planta daninha; carbono; C/N; weed biology; weed; carbon; mineral nutrition; C/N